2017
DOI: 10.4172/2161-0487.1000301
|View full text |Cite
|
Sign up to set email alerts
|

Attrition and Outcome in Group Psychotherapy among Traumatized and Non-Traumatized Inpatients

Abstract: Objective: To examine the impact of correlates of trauma on the appropriateness for group therapy (GT) in 60 participants based on the similarity of the exclusion criteria for GT to the features of posttraumatic disturbances and borderline personality. Method: We assessed the correlates of trauma (PTSD, complex PTSD, dissociation), features of BPD, psychopathological distress and the readiness for GT. Results: There were inverse correlations between the motivation for GT and multiple symptoms, as well as weak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In previous research, barriers to group format have included concerns about expressing emotions within a group setting, stigmatisation by the group, general disliking of the group composition and concerns about group participation (Kracen et al, 2013) Additionally, our study's treatment drop-out rate of 35% was higher than for average PTSD therapies (Lewis et al, 2020). However, many of our participants (69%) had high symptom severity and complex presentations, which has been acknowledged as a contributor to higher drop-out (Dorrepaal et al, 2012;Gene-Cos et al, 2016;McDonagh et al, 2005;Vogel et al, 2017). Given that stabilisation is hypothesised to improve treatment drop-out (Lewis et al, 2020) and given that services such as Plymouth Options deliver recovery-orientated psychological therapy, further improvement of uptake and attrition is important for this population and warrants further research.…”
Section: Feasibility and Acceptability Of The Groupmentioning
confidence: 82%
“…In previous research, barriers to group format have included concerns about expressing emotions within a group setting, stigmatisation by the group, general disliking of the group composition and concerns about group participation (Kracen et al, 2013) Additionally, our study's treatment drop-out rate of 35% was higher than for average PTSD therapies (Lewis et al, 2020). However, many of our participants (69%) had high symptom severity and complex presentations, which has been acknowledged as a contributor to higher drop-out (Dorrepaal et al, 2012;Gene-Cos et al, 2016;McDonagh et al, 2005;Vogel et al, 2017). Given that stabilisation is hypothesised to improve treatment drop-out (Lewis et al, 2020) and given that services such as Plymouth Options deliver recovery-orientated psychological therapy, further improvement of uptake and attrition is important for this population and warrants further research.…”
Section: Feasibility and Acceptability Of The Groupmentioning
confidence: 82%
“…CFT has been found to have good attrition among a variety of populations including those with dementia (94%; Collins et al, 2018), perfectionism (96%; Rose et al, 2018) and psychosis (82%; Laithwaite et al, 2009) and those in an inpatient setting (95%; Braehler et al, 2013). Given the challenges faced regarding interpersonal domains as described above, this has particular relevance, as populations with CPTSD may find it difficult to commit to a programme of treatment given these disturbances (16-20%; Vogel et al, 2017). In addition, several studies have measured individual satisfaction with CFT, with consistently high levels reported (Duarte et al, 2017;Graser et al, 2016;Clapton et al, 2018), although it is worth noting that populations with high shame may feel unable to give critical feedback, so these results should be interpreted cautiously.…”
Section: Acceptability and Viability Of Compassion-based Interventionsmentioning
confidence: 99%